Impact of the Fashion and Design Industry on Social Economic Development in Indonesia - Sinurat, Matius (International Journal of Fashion and Design, 2023)
Purpose: The study sought to analyze impact of the fashion and design industry on social economic development in Indonesia Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that the greatest perceived socio-economic impacts of the hospitality sector are increased employment, improved living standards, greater tax revenues to State and local governments and growth in local retail sales. The hospitality industry generates substantial direct and indirect revenues for local and regional economies. Unique Contribution to Theory, Practices and Policies: The Development theory and Export theory may be used to anchor future studies in the fashion and design sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management of fashion industries in the country will also use the study findings to improve development performance in all their activities and programs. The study recommends that the adoption of effective social protection development policies in the fashion and design sector will help to improve efficiency in their major operations and activities.